Solvent effects at the photoelectrode/electrolyte interface of a DSC: A combined spectroscopic and photoelectrochemical study - Stergiopoulos, T.; A. G. Kontos; V. Likodimos; Perganti, D.; P. Falaras (Journal of Physical Chemistry C, 2011)
The behavior of organic solvents typically used in redox electrolyte media for dye-sensitized solar cells (DSCs) has been systematically investigated by resonance Raman spectroscopy in combination with electrochemical impedance (EIS), intensity modulated photovoltage (IMVS), and photocurrent (IMPS) spectroscopies. Resonance Raman spectra reveal appreciable shifts in the vibrational frequency of the dye carboxyl anchoring groups as well as intensity variations of high- and low-frequency modes of dye-redox species by varying the electrolyte solvent and the polarization bias. These results are related to the variable surface coverage of the dye-TiO2 photoelectrode by solvent molecules determined by their donor number, the concomitant change on the concentration of dye-redox couple intermediate adducts, and the dye-TiO 2 electronic coupling. EIS and IMVS reveal a marked variation of the recombination kinetics and chemical capacitance of the corresponding DSCs, providing direct evidence for the shift of the TiO2 conduction band edge and deceleration of back-reaction kinetics. This accounts well for the solvent dependence of the device opencircuit voltage, whereas more complicated effects underlie the variation of the short-circuit current density that depends on electron injection. Tuning the solvents' function in DSCs may thus result in significant improvement of the DSC photovoltaic efficiency by effectively controlling electron energetics and injected photoelectron-triiodide recombination. © 2011 American Chemical Society.